Influence of Tertiary Activities on Transformation of the Rural Settlements in Bosnia and Herzegovina - Nurković, Rahman (Journal for Geography, 2010)
In Bosnia and Herzegovina, tertiary activities strongly affect the modern spatial and functional structure of rural settlements. In economic and social life they are complementary, which is a good prerequisite for general development of the country. They are followed by specialised shops (bank services, legal services, higher educational institutions, large market, diverse manpower, extensive public services, car show rooms, gas stations, furniture shops, commercial centres, hotels, motels, computer equipment, and alike).